Gain, amplified spontaneous emission and noise figure of bulk InGaAs/InGaAsP/InP semiconductor optical amplifiers. Issue 2 (1st April 2015) - Mazzucato, Simone; Carrère, Helene; Marie, Xavier; Amand, Thierry; Achouche, Mohand; Caillaud, Christophe; Brenot, Romain
Abstract : Bulk InGaAs layer under slight tensile strain, embedded in InGaAsP barriers and grown on InP, was used as semiconductor optical amplifier active layer for polarisation insensitive amplification. The material bandstructure was obtained by solving the Lüttinger–Kohn Hamiltonian, including tetragonal strain contribution. Study of the InGaAs material gain was performed by taking into account the effect of k‐dependent bandgap shrinkage. The semiconductor optical amplifiers device amplified spontaneous emission and noise figure have been investigated as a function of temperature, carrier density and barrier height. Good agreement was obtained with the trends observed in the experimental characteristics. The authors show that a 100 nm bandwidth can be obtained with a difference between transverse electric and transverse magnetic emission kept constant, as required for polarisation independent amplifiers.